PARP1 and PARP2 stabilise replication forks at base excision repair intermediates through Fbh1-dependent Rad51 regulation - George E. Ronson (Nature Portfolio, 2018)
PARP1 has a well characterised role in DNA break repair and base excision repair, whereas the role of PARP2 is less well understood. Here, the authors show a requirement for PARP2 in stabilising replication forks that encounter base excision repair intermediates.